Environmental Determinants of Fecal Microplastic Abundance: A Cross-Sectional Study in the Musi River Basin, Indonesia - Diah Navianti; Khairil Anwar; Miftahurrizqiyah (Poltekita: Jurnal Ilmu Kesehatan, 2026)
Background: Microplastics have been detected across multiple environmental compartments and can enter the human body through food and drinking water, representing an emerging concern in environmental toxicology related to chronic human exposure. Methods: A cross-sectional study was conducted among residents of the Musi River watershed, Indonesia, involving samples of refilled drinking water, tea products, and human feces. Microplastics were identified using digital microscopy and classified according to GESAMP guidelines. Associations between environmental exposure factors and fecal microplastic abundance were analyzed using correlation analysis and multiple linear regression. Results: Microplastics were detected in all analyzed matrices. Fecal microplastic abundance was significantly associated with duration of residence (r = 0.241, p = 0.041), consumption of refilled drinking water (r = 0.284, p = 0.037), and teabag consumption (r = 0.312, p = 0.021). Teabag consumption showed the strongest association; however, documented consumption patterns indicated that teabags were routinely prepared using refilled drinking water. In multivariate analysis, all three factors were independent predictors, explaining 31.2% of the variance (R² = 0.312; p < 0.05). Conclusion: Microplastics present in refilled drinking water and teabags represent an additional route of human exposure that should be considered in strategies to improve drinking water quality and reduce environmental health risks.